Pemanfaatan Teknologi untuk Informasi Kesehatan Gigi dan Mulut Serta Pendidikan Kesehatan Gigi dan Mulut - Hasrini Hasrini; Aisyah AR; Zulkarnain Zulkarnain; Zahrawi Astrie Ahkam; Amirah Maritsa (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
Many factors, including parents' knowledge of how to guide their children to maintain oral health, cause school-age children to often experience oral problems. Although technological advances have helped people get more information about health, they can also cause mistakes. By holding counseling, community service-based activities aim to improve the knowledge of students and parents/guardians of grade 4 of Minasa Upa State Elementary School about oral health and disseminate information about oral health through the internet. The activity was successful, with students and parents/guardians of grade 4 of Minasa Upa State Elementary School gaining better knowledge about oral health.